Bad Ragaz Ring Method Versus Halliwick Method in Verbally Cooperative Children with Spastic Cerebral Palsy (GMFCS Levels I–II): A Pilot Comparison Study - Na-Yeon Ye; Eun-Ju Lee (Journal of Clinical Medicine, 2026)
Background/Objectives: Aquatic therapy is widely used for children with cerebral palsy (CP), but existing approaches such as the Halliwick method focus primarily on postural control and mobility with limited active resistance exercise. The Bad Ragaz Ring Method (BRRM) integrates proprioceptive neuromuscular facilitation (PNF) diagonal patterns with closed kinetic chain (CKC) exercise in the aquatic environment, yet its direct application to children with spastic CP has rarely been examined. This pilot study compared the effects of BRRM and the Halliwick method on muscle thickness, strength, and balance in verbally cooperative children with spastic CP. Methods: Twelve children with spastic CP (Gross Motor Function Classification System [GMFCS] Levels I–II, aged 5–18 years) were randomly allocated to the BRRM group (n = 6) or the Halliwick group (n = 6), stratified by GMFCS level. Both groups received 40-min sessions twice weekly for 8 weeks (16 sessions). Transversus abdominis (TrA) and tibialis anterior (TA) muscle thickness, ankle dorsiflexion (ADF) strength, one-leg stance (OLS) duration, and Timed Up and Go (TUG) performance were assessed at baseline and after 2, 4, 6, and 8 weeks. A linear mixed model was used to analyze group × time interactions. Results: Significant group × time interactions were observed for TrA thickness (p = 0.02, partial η2 = 0.65), ADF strength (p < 0.01, partial η2 = 0.95), and OLS duration (p = 0.02, partial η2 = 0.66), with larger changes in the BRRM group. No significant between-group differences were found for TA thickness or TUG performance. Conclusions: In verbally cooperative children with spastic CP at GMFCS Levels I–II, BRRM was associated with larger changes than the Halliwick method in deep trunk muscle thickness, ankle dorsiflexion strength, and static balance. These preliminary findings support further investigation of BRRM in larger randomized controlled trials.